RISK TAKING CAPACITY AND ENTREPRENEURSHIP INCLINATION OF GRADUATES AMONG POSTGRADUATE STUDENTS IN PUBLIC UNIVERSITIES IN LAGOS STATE, NIGERIA - John Oluwaseun Ajamobe (Fakultas Ilmu Pendidikan-Universitas Negeri Malang, 2021)
The study examined risk-taking capacity and entrepreneurship inclination of graduates among postgraduate students in public universities, Lagos state, Nigeria. The study specifically examined the extent of relationship that exists between the risk-taking capacity factors namely: government regulatory policies, economic factors and business related factors as well as entrepreneurship inclination of graduates. Literature of related importance was reviewed. Three research questions were raised and three null hypotheses were tested to guide the study at .05 significant levels. The descriptive survey research design was adopted in the study. Simple random sampling technique was adopted to select 340 postgraduate students in public universities in Lagos State. A researcher designed questionnaire titled “Risk-Taking Capacity and Entrepreneurship Inclination Questionnaire” (RTCEIQ) was the validated instrument used to gather data in the study at r=.80 reliability value. The data collected was analyzed using descriptive statistics such as frequency coefficient, percentage, mean and standard deviation while Pearson Product Moment Correlation was used to test the three hypotheses generated for the study at p<0.05 level of significance. Findings of the study showed that government regulatory policies (r=.54; df= 328; P<.05), economic factors (r=.48; df= 328; P<.05) and business-related factors (r=.57; df= 328; P<.05) respectively were significantly correlated with entrepreneurship inclination of university graduates. The study recommends that graduates who are entrepreneurial driven should strive for proper assessment of risks and prioritizing them appropriately so as to ensure that resources are utilized profitably to tackle risks that are likely to emerge in infant business through provision of attractive packages and policies from insurance companies.